The Moderating Role of Self-Efficacy in the Influence of Participative Leadership Style and Teachers’ Professional Ethics on Students’ Learning Engagement: Peran Efikasi Diri dalam Memoderasi Pengaruh Gaya Kepemimpinan Partisipatif dan Etika Profesional Guru terhadap Keterlibatan Belajar Siswa - Anggreani, Bunga; Widhiastuti, Ratieh (Academia Open, 2026)
General Background: Student learning engagement is a central factor in educational success because it reflects students’ behavioral, emotional, and cognitive participation in academic activities. Specific Background: This study examined participative leadership style, teachers’ professional ethics, and self-efficacy within the framework of Social Cognitive Theory to explain student learning engagement. Knowledge Gap: Previous studies have commonly examined leadership, teacher professionalism, self-efficacy, and student engagement separately or through direct relationships, while integrated moderation models remain limited. Aims: This study aimed to analyze participative leadership style and teachers’ professional ethics in relation to student learning engagement, with self-efficacy as a moderating variable. Results: Using a quantitative survey design and Partial Least Squares analysis assisted by SmartPLS 4, the findings showed that participative leadership style had a positive and significant relationship with student learning engagement, while teachers’ professional ethics did not show a significant relationship. Self-efficacy had a direct positive relationship with student learning engagement but did not moderate the relationships between participative leadership style, teachers’ professional ethics, and student learning engagement. Novelty: The novelty lies in the simultaneous examination of participative leadership style, teachers’ professional ethics, and self-efficacy in one moderation model, showing that self-efficacy does not strengthen external factors in explaining student engagement. Implications: The findings indicate that student engagement is shaped more by active classroom participation and students’ self-belief, supporting the use of collaborative discussions, problem-based learning, and constructive feedback in learning activities. Highlights • Participative classroom leadership shows a significant positive relationship with student engagement.• Teachers’ professional ethics does not show a significant relationship in the tested model.• Self-efficacy contributes directly but does not act as a moderating variable. Keywords Participative Leadership; Self Efficacy; Student Engagement; Professional Ethics; Social Cognitive Theory